Amateur gold farming in China: “Chinese ingenuity,” independence and critique - Liboriussen, Bjarke (Sage, 2016)
Informed by a mix of theoretical sources and interviews with middle-class Chinese amateur gold farmers, this article argues that within China, the figure of the Chinese gold farmer might function as focus for reflection on Chineseness and China’s role in an increasingly interconnected world, rather than as a carrier of third-world stereotype as it tends to do in the West. The concept of shanzhai—often associated with sometimes comical, sometimes innovative Chinese copying of foreign con- sumer goods—is employed as a key analytical tool and helps highlight the themes of “Chinese ingenuity,” independence (from game operators and to some extent also parents), and critique (of games).